2015
DOI: 10.1007/s00421-015-3152-6
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin supplementation likely attenuates delayed onset muscle soreness (DOMS)

Abstract: Oral curcumin likely reduces pain associated with DOMS with some evidence for enhanced recovery of muscle performance. Further study is required on mechanisms and translational effects on sport or vocational performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(170 citation statements)
references
References 56 publications
8
152
0
2
Order By: Relevance
“…This study also reported a small reduction in a marker of muscle injury (i.e., CK) [179]. Similarly, McFarlin et al [180] reported a 48% reduction in CK after subjects consumed 400 mg/day of a highly bioavailable source of curcumin for 2 days before and 4 days after a high-intensity, muscle damage-inducing protocol.…”
Section: Curcuminmentioning
confidence: 61%
See 1 more Smart Citation
“…This study also reported a small reduction in a marker of muscle injury (i.e., CK) [179]. Similarly, McFarlin et al [180] reported a 48% reduction in CK after subjects consumed 400 mg/day of a highly bioavailable source of curcumin for 2 days before and 4 days after a high-intensity, muscle damage-inducing protocol.…”
Section: Curcuminmentioning
confidence: 61%
“…Nicol et al [179] reported that a dose of 5 g/day of curcumin reduced DOMS 24 and 48 h after high-intensity muscle-damaging exercise [179]. This study also reported a small reduction in a marker of muscle injury (i.e., CK) [179].…”
Section: Curcuminmentioning
confidence: 77%
“…Some investigations have evaluated for the effect of curcumin on DOMS (21)(22)(23)(24). However, to the best of our knowledge, no study to date has tested administration of 150mg curcumin supplement immediately after intensive eccentric exercise.…”
Section: Nakhostinmentioning
confidence: 99%
“…The effects of EIMD begin approximately 6 h after exercise, peak at 24-72 h, and subside 4-7 days after exercise [10][11][12]. Muscle damage is mainly induced by mechanical stress and disturbances of calcium homeostasis, and a perception of discomfort within the muscle may be developed [10].…”
Section: Introductionmentioning
confidence: 99%